Regulation of Energy Metabolism and Anti-Inflammatory Activities of Mastiha Fractions from Pistacia lentiscus L. var. chia - Foteini D. Kalousi; Federica Pollastro; Aikaterini G. Karra; Ioannis Tsialtas; Achilleas Georgantopoulos; Stefano Salamone; Anna-Maria G. Psarra (Foods, 2023)
Pistacia lentiscus L. var. chia resin (Chios Mastiha), the first natural chewing gum, is widely used in Mediterranean cuisine and has been used in traditional medicine from ancient times. Regarding its chemical composition, Chios Mastiha is known to be rich in triterpenes. Triterpenes have a similar structure to glucocorticoids (GCs), the steroid hormones that exert strong anti-inflammatory activities and play crucial roles in the regulation of cellular metabolism. To simplify the characterization of the bioactive compounds of Mastiha resin, three different polarity fractions were isolated and were further analyzed regarding their main chemical composition and an assessment of their biological activities. The biological assessment focused on the evaluation of the potential anti-proliferative, anti-inflammatory, and apoptotic activities as well as the possible interference of the three different polarity Mastiha fractions with the glucocorticoid receptor signaling, with the aim of characterizing the biochemical mechanisms of the actions of the Mastiha fraction. Applying MTT cell viability assay, luciferase/β-galactosidase assay, and Western blot analysis showed that Chios Mastiha apolar, medium-polar, and polar fractions reduced the HEK293 cell viability in a dose-dependent manner, possibly by mitochondrial-mediated induction of apoptosis. Medium-polar and polar Mastiha fractions also suppressed the GR and NF-κΒ transcriptional activation and the p65 protein levels. These activities were accompanied by the modulation of protein levels of regulatory molecules playing a crucial role in cellular energy homeostasis, such as GR, phosphoenolpyruvate carboxykinase (PEPCK), and/or peroxisome proliferator-activated receptor alpha (PPARα), and by the induction of phosphorylation and the activation of the AMP-activated protein kinase (AMPK). The medium-polar fraction was found to be enriched in triterpenes, such as lupeol, 24Z-masticadienonic acid methyl ester, and 24Z-isomasticadienonic acid methyl ester, and it was the most active one, so we propose that triterpenes in medium-polar fraction are possibly the bioactive compounds responsible for Mastiha’s regulatory actions on energy metabolism and anti-inflammatory activities via interference with GR, NF-κΒ, and AMPK signaling. This highlights its potential applications in many fields of pharmaceutical, cosmetic, and nutraceutical interest.